2018
DOI: 10.7196/samj.2018.v108i2.13035
|View full text |Cite
|
Sign up to set email alerts
|

Truvada (emtricitabine/tenofovir) pre-exposure prophylaxis roll-out among South African university students: Lots of positives, but let us keep an eye on possible surprises

Abstract: Antiretroviral therapy (ART) has fundamentally altered the natural history of HIV/AIDS, sharply reducing HIV-related morbidity and prolonging longevity. However, there seems to be a resurgence in HIV infection rates in some parts of the world that has prompted consideration of pre-exposure prophylaxis (pre-EP) and vaccination. Despite their good viral suppression profiles, most drugs used as part of ART also have unwanted adverse drug reactions/effects (ADRs). In this article we acknowledge the utility of pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For the musculoskeletal system, elevated creatine kinase was reported in up to 9% patients using Truvada. Decreased bone mineral density and bone fractures (Desai et al, 2017;Montjane, Dlamini, & Dandara, 2018;Mulligan et al, 2015) have also been reported, especially for people with vitamin D 3 deficiency, intake of Truvada would cause decrease of bone mineral density. Supplementation of vitamin D was suggested for PrEP users (Havens et al, 2019;Havens et al, 2019;Nanayakkara et al, 2019).…”
Section: Side Effects Of Prepmentioning
confidence: 99%
“…For the musculoskeletal system, elevated creatine kinase was reported in up to 9% patients using Truvada. Decreased bone mineral density and bone fractures (Desai et al, 2017;Montjane, Dlamini, & Dandara, 2018;Mulligan et al, 2015) have also been reported, especially for people with vitamin D 3 deficiency, intake of Truvada would cause decrease of bone mineral density. Supplementation of vitamin D was suggested for PrEP users (Havens et al, 2019;Havens et al, 2019;Nanayakkara et al, 2019).…”
Section: Side Effects Of Prepmentioning
confidence: 99%